2018
DOI: 10.1111/jpn.13009
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of humate–manganese complex for broilers fed a corn–soya bean meal diet

Abstract: The experiment was conducted to investigate the bioavailability of manganese (Mn) from humate–Mn complex relative to Mn sulphate for the starter broilers fed a conventional corn–soya bean meal diet. A total of 560 1‐day‐old Arbor Acres male broiler chicks were randomly allotted to one of eight replicate cages (10 chicks per cage) for each of seven treatments in a completely randomized design involving a 2 × 3 factorial arrangement of treatments with two Mn sources (humate‐Mn and Mn sulphate) and three levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…We found a correlation between Mn levels in the feed and blood of chickens raised on farms located <25 km away (r 2 = 0.24, p < 0.05), as shown in Table 8 . This is consistent with the report of Zhao et al (2019), who reported that the Mn concentrations in the plasma and heart of broilers increased linearly as dietary Mn concentration increased [ 83 ]. Furthermore, we also found a significant correlation between Cd in the feed and blood of ducks farmed nearest to the gold mine (r 2 = 0.95, p < 0.05; Table 8 ).…”
Section: Resultssupporting
confidence: 93%
“…We found a correlation between Mn levels in the feed and blood of chickens raised on farms located <25 km away (r 2 = 0.24, p < 0.05), as shown in Table 8 . This is consistent with the report of Zhao et al (2019), who reported that the Mn concentrations in the plasma and heart of broilers increased linearly as dietary Mn concentration increased [ 83 ]. Furthermore, we also found a significant correlation between Cd in the feed and blood of ducks farmed nearest to the gold mine (r 2 = 0.95, p < 0.05; Table 8 ).…”
Section: Resultssupporting
confidence: 93%